Epidemiological aspects of breast cancer incidence in Republic of Belarus - Batyan, Anatoliy N.; Kosteckaya, Tatyana V.; Lemiasheuski, Victor O. (Journal of the Belarusian State University. Ecology, 2020)
The results of a long-term retrospective epidemiological analysis of the incidence of breast cancer in the population of Belarus are presented. It is shown that in 35 years of observations, the incidence of the female population increased 4 times: from 16.3 0/0000 in 1971 to 64.8 0/0000 – in 2004. The standardPized incidence rate of women in the urban population increased in 2.5 times: from 19.2 0/0000 in the early 70s. to 48.9 0/0000 in 2004. The dynamics of the increase in the number of cancers for every 100,000 men over 10 years was 29.5 %, and for every 100,000 women – 23.8 %. The effect of gender on cancer incidence rates is manifested at the age of 55 years. From a socio-economic perspective, a special group is the working-age population (in 2017, women from 16 to 55.5 years and men from 16 to 60.5 years). According to the data of the Belarusian Cancer Registry over the last decade, the absolute number of newly detected cases of breast cancer in 2006 was 3,393 women, in 2007 – 3.606, 2010 – 3.931, 2011 – 3.889, 2015 – 4.324, 2016 – 4.428 and in 2017 – 4.616 new patients. In 2017, the timely diagnosis of early stages of breast cancer (stage I and stage II) reached 73.5 %, of which stage I was 31.0 % of cases. In 2017, the standardized incidence rate of women per 100,000 population corresponded to 52.6. It is assumed that only due to further aging of the female population, the annual number of new cases of breast cancer will steadily increase.